Pendekatan Model Ui Ux Aplikasi Mobile Penjualan Pada Toko Bandoeng Fasion Memanfaatkan Figma - Fauzan Muhamad Nur; Alex Wijaya (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
Instagram social media is used by Bandoeng Fasion as a medium to market products and aims to make it easier for consumers or potential buyers to find information about the products to be purchased and also aims to facilitate transactions. Product posts and the number of followers, are one of the indicators that can influence a consumer's trust and buying interest. The purpose of this study was to design an attractive, easy-to-use design and modern UI/UX for analytics applications for Bandoeng Fasion. So that it can increase engagement which has an impact on increasing trust and buying interest in consumers. The data needed in designing the UI / UX design was obtained by conducting a direct interview with the owner, namely Raniti. In designing this UI/UX, This, the editing software used is Figma. Figma is a web-based application for designing UI and UX that can use it for the creation of an application or web and its various user interface components With this research, it is hoped that it can make it easier for Bandoeng Fasion to design mobile-based applications